1997
DOI: 10.1007/bf02242458
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound transmission velocity of the proximal phalanxes of the non-dominant hand in the study of osteoporosis

Abstract: The aim of our study was to evaluate a quantitative ultrasound technique for measuring bone tissue at the proximal phalanxes of the non-dominant hand. We correlated the mean value of the amplitude-dependent speed of sound (AD-SoS) measured at the distal metaphysis of the last four proximal phalanxes with age, months since menopause and bone mineral density (BMD) of the lumbar spine in 264 women. We further assessed the ability of the AD-SoS to discriminate between normal and osteoporotic subjects with document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
2

Year Published

1999
1999
2002
2002

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 16 publications
9
22
2
Order By: Relevance
“…This again would stress that QUS and DXA quantify partially different bone 'qualities' and not BMD exclusively. In this context the documented moderate correlation between BMD and QUS measurements could be seen which confirms existing cross-sectional data [11,12].…”
Section: Quantitative Ultrasound At the Proximal Phalanges Of The Handsupporting
confidence: 86%
“…This again would stress that QUS and DXA quantify partially different bone 'qualities' and not BMD exclusively. In this context the documented moderate correlation between BMD and QUS measurements could be seen which confirms existing cross-sectional data [11,12].…”
Section: Quantitative Ultrasound At the Proximal Phalanges Of The Handsupporting
confidence: 86%
“…Our short-term precision of the technique in healthy subjects was similar to other reports of our research group and others [10,29,30]. This CV value was slightly increased when calculated in patients with synovitis.…”
Section: Discussionsupporting
confidence: 90%
“…The aim of this study was to assess the bone status in male PA patients evaluating the ultrasound transmission velocity through the proximal phalanges, which positively correlates with BMD of the lumbar spine [10], as well as the morphologic and energetic parameters of the trace score, which depend on the integrity of the bone structures traversed [11]. We also compared these findings with those of RA patients, whose peripheral osteoporosis is a well-known feature of the disease [12][13][14][15], and with those of ankylosing spondylitis (AS) patients, in whom there are conflicting data concerning the appendicular bone mass measurements [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Initial results also indicate the usefulness of phalangeal SOS in the assessment of rheumatoid arthritis [26,27] and disorders of growth and puberty in children [28]. It has been shown that AD-SoS allows the discrimination of osteoporotic from normal subjects [10,17,23].…”
Section: Introductionmentioning
confidence: 97%
“…With aging and osteoporosis the phalanges undergo morphologic changes such as widening of the medullary canal and increased tunneling in the cortex, which should be detectable by ultrasound. Using the DBMSonic 1200 (IGEA, Carpi, Italy) a signi®cant decrease in`Amplitude-Dependent Speed of Sound' (AD-SoS) due to aging [17,23,24], strongest in early postmenopausal women, and an increase in AD-SoS during hormone replacement therapy [25] have been observed. AD-SoS is the standard speed of sound parameter of the device, calculated as the ratio between transducer distance and time-of-¯ight (TOF) between the transducers.…”
Section: Introductionmentioning
confidence: 99%